Organic functional group analysis theory and development, - Schenk, George H. (The Commonwealth and international library. Selected readings in analytical chemistry, 1968)
Organic Functional Group Analysis: Theory and Development details the methods the best represent the progress in functional group analysis. In the second part, the title presents several papers that cover various areas in the field of functional group analysis. The text first covers the oximation of acetone and furfural, and then proceeds to tackling the utility of non-aqueous titrations. The selection also discusses how the determination of the per cent enol provides information which complements the per cent purity found by non-aqueous titration. Next, the title discusses the analytical adva.